Pengaruh Pemberian Air Lindi TPA-Sampah dan Pupuk NPK Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Main Nursery - Tengku Nurhidayah; Nur Habib Saputra; Muhammad Ali (Pelantar Press, 2025)
Palm oil is one of the plantation crops that produce vegetable oil, which is currently the main and priority agricultural commodity in Indonesia. The growth of palm oil seedlings is largely determined by good cultivation efforts such as the use of good planting media and the provision of nutrients. Adequacy of nutrients in the planting medium greatly affects the growth of the plant itself. This research aims to determine the interaction effect of giving TPA-Waste leachate and NPK fertilizer, to determine the single factor effect of TPA-Waste leachate and NPK fertilizer and to obtain the concentration of TPA-Waste leachate and the best NPK dosage for the growth of oil palm seedlings.This research was carried out experimentally in the form of a 4x4 factorial which was arranged according to a factorial Completely Randomized Design (CRD) consisting of two factors. The first factor is the concentration of leachate (L) which consists of 4 levels, namely L0 = without leachate (positive control), L1 = Leachate 100 ml.1-1 air, L2 = Leachate 200 ml. 1-1 water, and L3 = Leachate 300 ml.1-1 water. The second factor was the dose of NPK Fertilizer (P) which consisted of 4 levels, namely P0 = without applying NPK fertilizer, P1 = 25 % recommended dose recommendation, P2 = 50% recommended dose recommendation, and P3 = 100% recommended dose recommendation. Parameters observed included the increase in seedling height, the number of leaves, the increase in tuber diameter, root volume, seedling dry weight and root canopy ratio. The results showed that the interaction of giving 300 ml of leachate. 1-1 and NPK fertilizer 25 g per plant significantly increased the number of leaves, the diameter of the weevil and the root volume of the oil palm seedlings.